Nano-cockle shell powder and alginate as novel injectable bone filler: A preliminary formulation and characterization study - George, Penny; Abdul Hamid, Zariyantey; Abu Bakar, Md Zuki; Bharatham, B Hemabarathy (Life Sciences, Medicine and Biomedicine, 2024)
Cockle shells of the Anadara granosa species consist of 95-99% aragonite form of calcium carbonate (CaCO3) crystals. Aragonites are known to be denser which allows it to be incorporated, resolved and replaced by bone tissues over time when used in bone tissue grafting. An injectable biomaterial-based bone filler with appropriate injectability and biological properties was formulated using powdered cockle shells in nanoscale (nCSP) and sodium alginate (Alg). Initial attempts in formulating the bone filler using alginate and citric acid as a setting agent in the composition of nCSP: Alg of 60: 40, 70: 30 and 80: 20 wt.% produced variable results in the bone filler characterization. Characterization study of nCSP-Alg bone filler with 70:30 wt.% compositions showed excellent injectability (p